2019
DOI: 10.1101/735076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring putative ancient whole genome duplications in the 1000 Plants (1KP) initiative: access to gene family phylogenies and age distributions

Abstract: Polyploidy or whole genome duplications (WGDs) repeatedly occurred during green plant evolution. To examine the evolutionary history of green plants in a phylogenomic framework, the 1KP project sequenced over 1000 transcriptomes across the Viridiplantae. The 1KP project provided a unique opportunity to study the distribution and occurrence of WGDs across the green plants. In the 1KP capstone analyses, we used a total evidence approach that combined inferences of WGDs from Ks and phylogenomic methods to infer a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
14
2
Order By: Relevance
“…The L event corresponds to known WGD events in other species (Edger et al , 2017; Sollars et al , 2017; Unver et al , 2017; Ren et al , 2018; Li & Barker, 2020). For instance, Sollars et al .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The L event corresponds to known WGD events in other species (Edger et al , 2017; Sollars et al , 2017; Unver et al , 2017; Ren et al , 2018; Li & Barker, 2020). For instance, Sollars et al .…”
Section: Resultsmentioning
confidence: 92%
“…Nevertheless, they stated that it was unclear if this was two events or just one with skewed signal. Unver et al (2017) and Li & Barker (2020) recognized two lineage‐specific WGDs for O. europaea and F. excelsior , whereas the L event is shared by other Lamiales. We recovered 7524 gene trees of homologs that were used for mapping gene duplication events to the species tree surrounding the L event.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an abundance of papers have highlighted the difficulties and complexities of determining WGD events across the tree of life (Conover et al, 2018; Tiley et al, 2018; Li and Barker, 2019 [Preprint]; Li et al, 2019; Nakatani and McLysaght, 2019; Zwaenepoel and van de Peer, 2019 [Preprint]; Zwaenepoel et al, 2019). We add another dimension to this conversation by demonstrating that the different taxonomic levels from which we sample, such as the order or family, make a difference in support of previously identified WGDs (i.e., the Brassiceae triplication).…”
Section: Discussionmentioning
confidence: 99%
“…We add another dimension to this conversation by demonstrating that the different taxonomic levels from which we sample, such as the order or family, make a difference in support of previously identified WGDs (i.e., the Brassiceae triplication). Recent research has demonstrated that differences in taxonomic sampling and taxon occupancy in data matrices can influence the inference of WGDs, particularly if adding taxa decreases taxon occupancy in gene families (Yang et al, 2015; Li et al, 2018; Li and Barker, 2019 [Preprint]; Zwaenepoel and van de Peer, 2019 [Preprint]). Testing for WGD events across the Brassicales phylogeny led to less certain topologies; therefore, signals of WGD are missed when filtering for nodes with only high bootstrap support to count duplicates.…”
Section: Discussionmentioning
confidence: 99%
“…Reference transcriptomes will differ from genomes in that not all loci will be represented by transcripts present in a given sample, not all transcripts will be assembled to full length, and the assembly will vary in the degree to which splice variants, alleles, and paralogs will occur as unique sequences or be merged (Meyer et al, 2011; Yang and Smith, 2013; Carpenter et al, 2019; Patterson et al, 2019). These issues will reduce the number of TagSeq reads that can be uniquely mapped to the reference, relative to a full genome, and they may be particularly problematic in plants where gene and genome duplications are common (Barker et al, 2016; One Thousand Plant Transcriptomes Initiative, 2019; Li and Barker, 2020), although sequencing at the variable 3′ untranslated region (UTR) should maximize locus discrimination (Rise et al, 2004).…”
mentioning
confidence: 99%